Pain in dementia - Bombón-Albán, Paulina E. (2022)
Rasmussen’s encephalitis is an unusual clinical entity characterized by drug-resistant focal epilepsy, neurological deficit and progressive cerebral hemiatrophy. The diagnostic and therapeutic approach is complex, even more so in patients with Rasmussen’s encephalitis of late onset (in adolescence and adulthood) whose clinical picture could be atypical when compared with its occurrence in children. We report a series of three clinical cases of late-onset Rasmussen’s encephalitis confirmed by histopathology and immunohistochemistry evaluations and in which clinical improvement was achieved after surgical interventions. Literature reviews on the clinical evolution and therapeutic alternatives for this type of presentation are included.